2009
DOI: 10.1111/j.1439-0469.1996.tb00810.x
|View full text |Cite
|
Sign up to set email alerts
|

Allozyme and morphology evolution in European Viviparidae (Mollusca: Gastropoda: Architaenioglossa)

Abstract: The paper describes morphometric and allozymic differences among four European species of the family Viviparidae: Viviparus contectus (Millet, 1813), V. viviparus (Linnaeus, 1758), V. acerosus Bourguignat, 1862, and V. ater (Cristofori et Jan, 1832). Fourteen continuous biometrical characters were measured. Incremental discriminant‐function analysis, principal‐component analysis, and non‐metric multidimensional scaling were applied to analysis of the morphometric differences. All the techniques confirmed a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The characteristic network of pores is found in Bithynia, Pseudobithynia (see above), Bythinella, also in Emmericia (see Appendix 2), but not in the Amnicolidae (a secondary loss?). The network occurs in Peringia (FISH & FISH 1977, FALNIOWSKI et al 1996, but is not found in the Hydrobiidae considered in the present paper. The irregular, very small pores were found in amnicolids as well as "pyrgulids".…”
Section: Evolution Of Morphological Charactersmentioning
confidence: 64%
“…The characteristic network of pores is found in Bithynia, Pseudobithynia (see above), Bythinella, also in Emmericia (see Appendix 2), but not in the Amnicolidae (a secondary loss?). The network occurs in Peringia (FISH & FISH 1977, FALNIOWSKI et al 1996, but is not found in the Hydrobiidae considered in the present paper. The irregular, very small pores were found in amnicolids as well as "pyrgulids".…”
Section: Evolution Of Morphological Charactersmentioning
confidence: 64%
“…The aim of this paper was to test its distinctness and phylogenetic relationships within Viviparus applying DNA markers. Some time ago the phylogeny of the other European viviparid species was reconstructed on the basis of morphological and allozymic characters (fAlniowski et al 1993a(fAlniowski et al , 1996a(fAlniowski et al , b, c, 1997(fAlniowski et al , 1998. Thus there was an opportunity to compare morphology-, allozyme-and DNAbased phylogenies.…”
Section: Introductionmentioning
confidence: 99%
“…The literature provides many examples of the increase of the number of embryos and their development advancement with the female's size (SPIGHT 1976, FALNIOWSKI et al 1996, MIDDELFART 1994, CHUNG et al 2002: the largest females carry the highest number of fully developed embryos while in the smallest females single, least developed embryos are sporadically noted. I found a similar relationship in the isolated Lake Bia³e where the mean number of embryos in the last growth stage (embryos with developed shell) increased with the female's shell height and body mass.…”
Section: Resultsmentioning
confidence: 99%